Enhancing the Solubility of Indrapuri Clay (Local “Kieserite”Fertilizer) - M. Adlim; Zarlaida Fitri; . Sulastri; Ratu Fazlia Inda Rahmayani; Yuliza Laini (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2012)
Study on enhancing the solubility of clay containing magnesium of localproduction (Indrapuri) has been conducted. The clay is commercially available and named as “kieserite” produced by local companies. The sample was taken randomly from fertilizer shops and analysed with AAS and XRF methods. XRF data of local kieserite showed the dominated chemical content; MgO(33.19%); SiO2(33.11%); CaO(1.90%);Al2O3 (5.77%) and Fe2O3(6.32%). The MgO content is higher than that of magnesium sulphate monohydrate (CAS No.: 14168-73-1) which is only 28%. The concentration of soluble magnesium ions of local kieserite naturally soluble was 0.0186% which is very low compared with the soluble magnesium of magnesium sulphate monohydrate (CAS No.:14168-73-1) which is 25%. The Enhancing the magnesium solubility was done by soaking the local kieseriteinto 0.1-0.5M HNO3 before neutralized with NH4OH or mixing the local kieserite with in alluvial, entisol, red-yellow-podsolik (RYP) soils with and without addition of 0.1-0.5M of (NH4)2SO4. The amount of dissolved magnesium of kieserite was found morein entisol soil than the other type of soils. The concentration increased up between 0.59-1.00% along with the incrementof (NH4)2SO4 concentration (0.1-0.5 M). Both in entisol soil and in 0.1 M of (NH4)2SO4, the dissolved magnesium ion increased up to 0.825% but decreased at higher concentration of (NH4)2SO4